Psychosocial Study on the Incidence of Postpartum Blues - Ruri Yuni Astari; Yeti Yuwansyah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The transition to motherhood is difficult because of changes in psychological, social and physiological aspects and an increase in the risk of mental illness and postpartum blues. This study aims to determine the incidence and the most influential factors of postpartum blues in light of the psychosocial aspect in the Majalengka District. This was a quantitative study with a cross-sectional design. The study subjects were normal postpartum women on days 5-14. The study samples involved 91 women who were selected using consecutive sampling techniques. The study was conducted in 14 Community Health Centers located in the work area of the Majalengka District Health Office on October 12 - November 11, 2020. Data were collected using the Edinburgh Postnatal Depression Scale (EPDS) and the husband support questionnaire. Data were analyzed using the chi-square statistical test and logistic regression. The results showed that there was a significant relationship between age (p = 0.008), income (p = 0.030), parity (p = 0.011), and husband support (p = 0.009) with the incidence of postpartum blues. The analysis of the dominant factor for the incidence of postpartum blues showed that postpartum women aged less than 20- more than 35 years had 5 times the chance (OR= 5.524) to have postpartum blues compared to postpartum women aged 20-35 years. Healthcare workers must be able to detect and diagnose the signs and symptoms of postpartum blues as early as possible and take immediate follow-up to reduce the risk factors for this condition. Abstrak: Transisi menjadi ibu adalah kondisi masa sulit karena adanya perubahan pada aspek psikologis, sosial dan fisiologis serta meningkatkan risiko penyakit mental terjadinya postpartum blues. Penelitian ini bertujuan untuk mengetahui kajian psikososial postpartum blues dan faktor yang paling berpengaruh di Kabupaten Majalengka. Studi ini merupakan penelitian kuantitatif dengan desain crossectional. Subjek penelitian adalah ibu nifas normal hari ke 5-14 dengan sampel sebanyak 91 menggunakan teknik pengambilan sampel consecutive sampling. Penelitian dilakukan di 14 puskesmas yang berada di wilayah Dinas Kesehatan Kabupaten Majalengka pada tanggal 12 Oktober-11 November 2020. Pengumpulan data menggunakan kuesioner Edinburgh Postnatal Depression Scale (EPDS) dan kuesioner dukungan suami. Analisis data menggunakan uji statistik chi-square dan regresi logistik. Hasil penelitian menunjukkan bahwa terdapat hubungan yang signifikan antara faktor usia p= 0,008, fakor penghasilan p= 0,030, faktor paritas p= 0,011 dan faktor dukungan suami p= 0,009 dengan kejadian postpartum blues. Faktor dominan terhadap kejadian postpartum blues menunjukkan bahwa ibu nifas dengan usia 20-35 tahun mempunyai peluang 5 kali (OR= 5,524) terjadinya postpartum blues dibandingkan ibu nifas dengan usia 20-35 tahun. Petugas kesehatan harus dapat mendeteksi dan mendiagnosis sedini mungkin terkait tanda dan gejala postpartum blues dan melakukan tindak lanjut segera untuk mengurangi faktor risiko kejadian ini.